2015
DOI: 10.1016/j.stemcr.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Synuclein Expression in the Oligodendrocyte Lineage: an In Vitro and In Vivo Study Using Rodent and Human Models

Abstract: SummaryIn this study, we sought evidence for alpha-synuclein (ASYN) expression in oligodendrocytes, as a possible endogenous source of ASYN to explain its presence in glial inclusions found in multiple system atrophy (MSA) and Parkinson’s disease (PD). We identified ASYN in oligodendrocyte lineage progenitors isolated from the rodent brain, in oligodendrocytes generated from embryonic stem cells, and in induced pluripotent stem cells produced from fibroblasts of a healthy individual and patients diagnosed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 28 publications
3
102
1
1
Order By: Relevance
“…Although not statistically significant, SNCA mRNA level may be increased in MSA compared with control brains 86. Subsequently, Djelloul and colleagues identified SNCA transcripts in oligodendrocyte lineage cells, including embryonic stem cell and induced pluripotent stem cell-derived oligodendrocytes from patients with MSA 81. This finding is in line with those of Asi’s study, but it remains to be determined whether the SNCA transcripts identified are reminiscent of basal expression in quiescent oligodendrocyte precursor cells.…”
Section: Controversiesmentioning
confidence: 56%
See 2 more Smart Citations
“…Although not statistically significant, SNCA mRNA level may be increased in MSA compared with control brains 86. Subsequently, Djelloul and colleagues identified SNCA transcripts in oligodendrocyte lineage cells, including embryonic stem cell and induced pluripotent stem cell-derived oligodendrocytes from patients with MSA 81. This finding is in line with those of Asi’s study, but it remains to be determined whether the SNCA transcripts identified are reminiscent of basal expression in quiescent oligodendrocyte precursor cells.…”
Section: Controversiesmentioning
confidence: 56%
“…This finding is in line with those of Asi’s study, but it remains to be determined whether the SNCA transcripts identified are reminiscent of basal expression in quiescent oligodendrocyte precursor cells. Furthermore, α-synuclein expression decreased during oligodendrocyte maturation 81. Taken together, SNCA transcripts identified in oligodendrocyte lineage cells may not be the origin of α-synuclein in GCIs in MSA.…”
Section: Controversiesmentioning
confidence: 83%
See 1 more Smart Citation
“…Another option is that a dysfunction in the clearance machinery is a prerequisite for α-syn uptake and/or accumulation in oligodendrocytes. In both scenarios, the oligodendroglial accumulation of α-syn may be further potentiated by increased expression of its gene (Asi et al, 2014; Djelloul et al, 2015) and oligo-dendrocyte-to-oligodendrocyte propagation. Finally, other suggested mechanisms are the involvement of altered iron metabolism in oligo-dendrocytes (Visanji et al, 2013), and epigenetic and/or environmental factors (Sturm et al, 2016).…”
Section: The Neuropathology Of Msamentioning
confidence: 99%
“…GCIs have a triangular or sickle-like morphology (Miki et al, 2010;Grazia Spillantini et al, 1998) and occur predominantly in oligodendrocytes (Ahmed et al, 2012). Although oligodendrocyte lineages are known to express α-syn mRNA at low levels both normally and in MSA, α-syn is expressed primarily in neurons, implicating uptake as the main source of α-syn in GCIs (Asi et al, 2014;Djelloul et al, 2015).…”
Section: Alpha-synuclein In Diseasementioning
confidence: 99%